The Effect of Family Based Interpersonal Psychotherapy on Depression in Patients with Major Depressive Disorder - อินทร์พันธ์ มลฤดี; อุปเสน รัชนีกร (Journal of The Royal Thai Army Nurses, 2019)
This study was a quasi-experimental study. The objectives of the study were to compare depression in patient with major depressive disorder before and after family based interpersonal psychotherapy and between group of patient who receive family base interpersonal psychotherapy and normal therapy. Sample a total of 40 Participants age 20-59 years old are patient who were diagnosed with major depressive disorder and receive treatment as Out Patient at King Chulalongkorn Memorial Hospital. Instruments used were 1) Personal Information Inquiries 2) Hamilton Rating Scale for Depression (HRSD-17) 3) Thai interpersonal Questionnaire Result 1. The statification on depression scores of depressed patients after family-based interpersonal psychotherapy were significantly lower than before the program at .05 level 2. The statification on depression scores of depressed patients after family-based interpersonal psychotherapy and normal treatment were significant difference at the .05 level